Sound navigation aid system for the vision impaired - Mohd Saufee, Muhammad; Thoo, Y. W.; Masra, S.M.W. (IEEE, 2013)
Visually impaired or blind people are someone who lost their ability to see. They usually depend on guide cane or guide dog to assist them navigates their environment. However, guide cane requires the blind to scan the surrounding manually with their hand while guide dog is expensive and has a short life span. There are many researches on creating better navigation aid for blind people. Instead of using vibration or alarm to notify the distance of the obstacles, this research proposed the application of sound notification for the blind. This system is developed using MATLAB r2010a with the integrated webcam of the laptop and a laser pointer. The laser pointer acts as a reference point so that object's distance can be calculated from the captured image by the webcam. This system manages to calculate distance for any color of object under any level of brightness condition during day and night time. It also possesses human head movement ability to turn left and right, up and down. This system managed to detect the obstacles up to a distance of 432 centimeters, which is sufficient to prevent the blind from bumping into the obstacles. The calculated distance is then converted to sound in order to notify the blind how far the object is away from them.